2016
DOI: 10.1371/journal.pone.0167400
|View full text |Cite
|
Sign up to set email alerts
|

Reward Contingencies Improve Goal-Directed Behavior by Enhancing Posterior Brain Attentional Regions and Increasing Corticostriatal Connectivity in Cocaine Addicts

Abstract: The dopaminergic system provides the basis for the interaction between motivation and cognition. It is triggered by the possibility of obtaining rewards to initiate the neurobehavioral adaptations necessary to achieve them by directing the information from motivational circuits to cognitive and action circuits. In drug addiction, the altered dopamine (DA) modulation of the meso-cortico-limbic reward circuitry, such as the prefrontal cortex (PFC), underlies the disproportionate motivational value of drug use at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 108 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…Cognitive control alterations in cocaine addiction are related to poor inhibitory control over craving, related to the frontal and parietal regions . However, monetary reward contingencies seem to enhance goal‐directed behavior in cocaine addicts . These results suggest that drug‐alternative reward contingencies (eg, monetary, familiar, social, and labor) may encourage cocaine‐dependent patients to be involved in treatment goals, such as longer periods of abstinence and treatment compliance, by improving cognitive control processes by the interaction of cognitive and motivational processes accordingly.…”
Section: Introductionmentioning
confidence: 93%
“…Cognitive control alterations in cocaine addiction are related to poor inhibitory control over craving, related to the frontal and parietal regions . However, monetary reward contingencies seem to enhance goal‐directed behavior in cocaine addicts . These results suggest that drug‐alternative reward contingencies (eg, monetary, familiar, social, and labor) may encourage cocaine‐dependent patients to be involved in treatment goals, such as longer periods of abstinence and treatment compliance, by improving cognitive control processes by the interaction of cognitive and motivational processes accordingly.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, we speculate that males players may prefer risk decision-making activities. Anyway, these results suggested that strong rewards and the impulse to pursue rewards [ 61 ] seem to be more pronounced in males. This may be the reason why male players are more likely to have IGD.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have examined neural responses to monetary reinforcers and showed a mixture of results, including increases, decreases, or no differences in reward-related activations among CDs, relative to HCs ( Goldstein et al, 2007 ; Jia et al, 2011 ; Patel et al, 2013 ; Bustamante et al, 2014 ; Balodis et al, 2016 ; Konova et al, 2016 ; Rosell-Negre et al, 2016 ; Rose et al, 2017 ). Some reported higher activation to monetary reinforcer in the caudate, putamen, insula, hippocampus, or cingulate gyrus in CDs compared with HCs ( Jia et al, 2011 ; Konova et al, 2016 ; Rose et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%